Scaling Up Patient-Centered Psychological Treatments for Perinatal Depression in the Wake of a Global Pandemic - Singla, Daisy R.; Meltzer-Brody, Samantha; Savel, Katarina; Silver, Richard K. (Frontiers in Psychiatry, 2022)
There is a call to action to reduce the public health burden of perinatal depression worldwide. The COVID-19 pandemic has further highlighted significant gaps in perinatal mental health care, especially among women who identify as Black, Indigenous and Persons of Color (BIPOC). While psychotherapeutic (cognitive, behavioral and interpersonal) interventions are endorsed for perinatal mood disorders, barriers to access and uptake contribute to inequitable access to treatment at the population level. To effectively address these barriers and increase the scalability of psychotherapy among perinatal women, we suggest four pragmatic questions to be answered from a patient-centered lens; namely, ‘who’, ‘what’, ‘how’, and ‘when.’ Promising avenues include task-sharing among mental health non-specialists, an emphasis on culturally sensitive care, web-based delivery of psychotherapy with some caveats, and a lifespan approach to perinatal mental health. Innovative research efforts are seeking to validate these approaches in diverse contexts across North America and the UK, lending optimism towards scalable and long-term solutions for equitable perinatal mental health care.